The Effect of Scaffolding Method on Fisrt-Year Students' Self-Confidence in Speaking at SMAN 2 Parepare - Rezki, Miftahul; Badaruddin; Ammade, Salasiah (English Education Study Program, 2025)
This study aimed to investigate the effect of the scaffolding method on students’ self-confidence in speaking at UPTD SMAN 2 Parepare. Preliminary observations revealed that one class of first-year students displayed notably higher self-confidence compared to others, which was linked to the implementation of the scaffolding method in that class. To assess the method's impact, an ex-post facto design with a quantitative approach was employed, focusing on the class, X.IPS.II, which consisted of 26 students. Data were collected using two questionnaires—one for the scaffolding method (X variable) and another for students' self-confidence in speaking (Y variable)—and supplemented with an observation checklist to validate the questionnaire data. Analysis was performed using IBM SPSS Version 25. Pearson’s product-moment correlation coefficient indicated an r-value of 0.888 between the scaffolding method and students’ self-confidence, surpassing the r-table value of 0.388, thus confirming a significant effect of the scaffolding method on students’ self-confidence in speaking which is classified into very strong